2015
DOI: 10.1515/ijamh-2015-0091
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management adapted for African-American adolescents with obesity enhances youth weight loss with caregiver participation: a multiple baseline pilot study

Abstract: This study demonstrates application of a novel experimental approach to intervention development and demonstrated the importance of parent involvement when delivering contingency management for minority youth weight loss. Lessons learned from contingency management program implementation are also discussed in order to inform practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…It was hypothesized that greater caregiver involvement in treatment would be associated with greater weight loss . 30…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that greater caregiver involvement in treatment would be associated with greater weight loss . 30…”
Section: Resultsmentioning
confidence: 99%
“…A 2015 review of the influence of parental participation on weight outcomes in African American adolescent females also concluded that strong parental involvement in obesity related interventions can facilitate weight loss and promote improved dietary intake and increased physical activity [26]. Furthermore, the incorporation of extrinsic motivation strategies [Contingency Management] benefits from parental involvement [19]. However, there was a subset of families that found the experience challenging at times, especially when there was minimal or no weight loss.…”
Section: Issn: 2469-4185mentioning
confidence: 99%
“…Motivational interviewing focuses on the compassionate elicitation and strengthening of intrinsic motivation for behavior change [16]. In addition, some families were randomized to receive Contingency Management [CM], extrinsic motivational content using operant conditioning principles to encourage completion of behavioral goals to address motivational barriers to weight loss [17][18][19]. At baseline families were randomized to receive MI-CBS either in the home or the office.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with those findings, both Petry et al 31 and Riaff and Dallery 32 conducted pilot tests of clinic-based incentives for SMBG, without any additional counseling or parent-led CM, and also found improvements in SMBG and glycemic control. Last, Hartlieb et al 33 conducted a pilot test of CM combined with behavioral skills training (BST) to enhance adolescent weight loss, and found that parent-involved CM, but not adolescent-only CM, enhanced the effect of BST on youth weight loss.…”
Section: Targeting Other Health Behaviors In Adolescentsmentioning
confidence: 99%